Eksistensi Lembaga-Lembaga Negara Independen dalam Mewujudkan Sistem Pemerintahan Demokratis dan Konstitusional - Hadji, Kuswan; Azizah, Anisa Fitriani; Aulia, Putri; Pandini, Anindya Intan; Oktasani, Reda; Patmawati, Nanda (Cattleya Darmaya Fortuna, 2025)
In a democratic and constitutional government system, independent state institutions have an important role in maintaining the balance of power, promoting transparency, and protecting human rights. Institutions such as the General Election Commission (KPU), Ombudsman and other supervisory bodies are needed to ensure constitutional principles are implemented effectively. The presence of these institutions is essential to monitor government actions, protect civil rights, and prevent abuse of power. This article examines the contribution of these independent institutions in achieving just and participatory governance, as well as the challenges they face. For these institutions to function optimally and achieve a more mature and sustainable democracy, support from government, society and international organizations is essential. This research uses a normative research method, namely by collecting data through a literature review with reference to several articles, references and appropriate legal bases.